Amores perros - Arriaga, Guillermo; Echevarria, Emilio; Bernal, Gael Garcia; Toledo, Goya; Iñárritu, Alejandro González; Altavista Films (Firm). ([Place of distribution not identified] Altavista Films, 2000)
A horrific car accident connects three stories, each involving characters dealing with loss, regret, and life's harsh realities, all in the name of love
"Summary taken from https://www.imdb.com/title/tt0245712
Produced by Guillermo Arriaga ; music, Gustavo Santoalalla; cinematography, Rodrigo Prieto.
Emilio Echeverria, Gael Garcia Bernal, Goya Toledo.
DVD
In Spanish with subtitles in English.
Keywords: Drama; Thriller